Variation in seed morphology in the genus Erica L. (Ericaceae) - Szkudlarz, Piotr (Biodiversity: Research and Conservation, 2010)
Seed morphology was studied in 136 species of Erica, including 123 from South Africa (Cape Floristic Region), 5 from tropical Africa, and 8 from Europe. Seed anatomy was studied in 13 selected species by light and scanning electron microscopy. Seed morphology of each species was described and documented by SEM micrographs. Ten major diagnostic features were selected, concerning seed shape, primary sculpture, and fine relief. On the basis of these features, the species were divided into 14 groups. Within them, 40 morphologically homogeneous subgroups were distinguished, which could possibly be used in future revisions of the genus. A key to species identification has been developed on the basis of seed characteristics. A very close similarity was observed between seeds of some Erica species from distant parts of the distribution range of this genus.